Aesthetics in design science research. Issue 2 (4th March 2018) - Baskerville, Richard L.; Kaul, Mala; Storey, Veda C.
Abstract: Much research has focused on understanding design science research and providing guidelines for its successful execution. However, there is still a need for more work on the raison d'être of design science research, which is the development of artefacts that can be applied to solve real-world problems. The value of design science research thus far has been to provide practically applicable solutions, as well as a contribution to knowledge. This paper proposes aesthetics, in addition to truth and utility, as a way to advance this raison d'être . We identify the design science triad of analytics, synthetics, and aesthetics and justify why the aesthetics quality attribute should be appreciated. We then identify twelve quality criteria for articulating and assessing aesthetics in design science research. Doing so enables us to both recognise and achieve artful design so that rigour, utility, and aesthetic value can collectively justify a valuable design science research contribution.